How do you expand (x-1)3 using binomial expansion?

A binomial expression is an expression containing two terms joined by either addition or subtraction sign. For instance, (x + y) and (2 – x) are examples of binomial expressions.

Binomial Theorem

The Binomial Theorem states the algebraic expansion of exponents of a binomial, which means it is possible to expand a polynomial (a + b)n into the multiple terms.

\((a+b)^{n} =\sum_{k=0}^{n}\begin{pmatrix} n\\ k \end{pmatrix}a^{n-k}b^{k}\)

Binomial formula to expand (a+b)3

Binomial formula for (a+b)33C 0 a 3 b 0 +3C 1 a 2 b 1 +3C2a 1 b 2 +3C 3 a 0 b 3 + ……..

Expand (x-1)3

So using the above formula we will expand (x-1)3

Here, a=x and b=-1.

3C 0 x 3 +3C 1 x 2×(-1) 1 +3C 2 x 1 ×(-1) 2 +3C 3 ×(-1) 3

We know that

3C 0 =3C 3 =1

3C 1 =3C 2 =3

On substituting above values in the above equation we get

x 3 -3x 2 +3x – 1

Answer

(x-1)3= x 3 -3x 2 +3x – 1

Leave a Comment

Your email address will not be published. Required fields are marked *

BOOK

Free Class